SESAT PIKIR DALAM TUTURAN WARGANET DI FACEBOOK (LOGICAL FALLACIES IN INTERNET CITIZEN SPEECH ON FACEBOOK) - Yoga Tri Adhi (Universitas Lambung Mangkurat, 2022)
Logical Fallacies in Internet Citizen Speech on Facebook. This study aims to understand the form of logical fallacies in the speech of internet citizens on Facebook. This research is a qualitative research. This type of qualitative approach is based on the logical context of the language on Facebook. The data of this research are internet citizens utterances which are identified as logical fallacies. The data collection technique used is documentation technique. The data analysis technique is done by reducing the data, display the data, and drawing conclusions. The technique of checking the validity of the data is carried out by means of persistence/regularity of observation of the form of logical thought that is displayed. The results of the research obtained are that there are ten types of logical fallacies that occur in five news topics that are selected with a certain logical form, namely: red herring, the strawman fallacy,ad hominem, false dilemma, hasty generalization, prejudicial language, appeal to faith, argument from ignorance, slippery slope, and weak analogy.Key words: logical fallacies, language, logic, social media, philosophySesat Pikir dalam Tuturan Warganet di Facebook. Penelitian ini bertujuan untuk memahami wujud sesat pikir dalam tuturan warganet di Facebook. Penelitian ini merupakan penelitian kualitatif. Jenis pendekatan kualitatif ini didasarkan pada konteks logika berbahasa di Facebook. Data penelitian ini adalah tuturan warganet yang teridentifikasi sebagai sesat pikir. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi. Teknik analisis data dilakukan dengan cara reduksi data, penyajian data, dan penarikan simpulan. Teknik pemeriksaan keabsahan data dilakukan dengan cara ketekunan/keajegan pengamatan terhadap wujud sesat pikir yang ditampilkan. Hasil penelitian yang diperoleh menunjukkan adanya sepuluh jenis sesat pikir yang terjadi pada lima topik berita yang dipilih dengan bentuk logika tertentu, yaitu: red herring, strawman fallacy, ad hominem, false dilemma, hasty generalization, prejudicial language, appeal to faith, argument from ignorance, slippery slope, dan weak analogy.Kata-kata Kunci: sesat pikir, logika, bahasa, media sosial, filsafat